Myoxanthus vittatus (Orchidaceae), a new species from Costa Rica - Pupulin, Franco; Blanco, Mario A. (Lankesteriana: International Journal on Orchidology, 2016)
The taxonomic position of Myoxanthus Poepp. & Endl. (Orchidaceae: Pleurothallidinae) i s d i s c u s s e d a n d Silenia L u e r i s m a i n t a i n e d a s a s u b g e n u s o f M y o x a n t h u s. A n e w s p e c i e s o f Myoxanthus is described and illustrated. Myoxanthus vittatus Pupulin & M.A. Blanco is apparently endemic to the low, tropical wet forests of central Pacific Costa Rica, where it has been collected in two different places. It differs from closely related species for the small size of the plant, the whitish flowers, longitudinally striped with purple, the densely pubescent ovary, and the ligulate, obtuse lip. The new combination Myoxanthus tomentosus (Luer) Pupulin & M.A. Blanco is proposed.